The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Arboricultural cut type and pruning severity can alter the arboreal invertebrate community for at least two years - Stella R. Dee; Michael J. Cunningham-Minnick; Athena P. Vasilopoulos; Brian Kane (Urban Forestry & Urban Greening, 2026)

Blood–Brain Barrier Permeability in Cases of Post-operative Delirium Is Associated with Central Nervous System Phosphatidylcholine Imbalances - Mijin Jung; Xiaobei Pan; Aoife Sweeney; Anthony P. Passmore; Bernadette McGuinness; Daniel F. McAuley; David Beverland; Amanda J. Heslegrave; Jonathan Schott; Henrik Zetterberg; Emma L. Cunningham; Brian D. Green (Molecular Neurobiology, 2026)
Blood-brain barrier (BBB) permeability is reportedly increased in patients exhibiting postoperative delirium. Changes in either cerebrospinal fluid (CSF) or blood metabolites have also been reported in cases of delirium. This investigation examined whether BBB permeability influences metabolite concentrations on either side of the barrier, and whether this changes in cases of delirium. This study is a nested case-control cohort ( n = 54) drawn from the entire cohort of n = 315 participants. Preoperative CSF and plasma from postoperative delirium and control participants matched for age and gender underwent metabolomic profiling. Concentrations of metabolites in plasma and in CSF were obtained, and where measurable, a CSF/plasma metabolite ratio (Qmetab) was calculated. CSF/plasma albumin ratio (Qalb), a recognized indicator of BBB permeability, was also calculated. The above parameters were compared between delirium and control groups. Finally, each Qmetab was correlated against Qalb for control or delirium cases. In cases where delirium would later occur there were significant elevations in the Qmetabs of amino acids (Gln, His, Met, Phe, Tyr and Val), and one phosphatidylcholine (PC). Many other PC Qmetabs significantly correlated with Qalb and this mainly occurred in individuals subsequently experiencing delirium. In persons prone to postoperative delirium, the equilibrium of certain species of PC across the BBB correlates with BBB permeability. It is unclear whether this occurs because of changes in PC metabolism or transit, but understanding this could improve our understanding of the mechanisms underlying delirium.

NextGen In A Box (NGIAB): Open-Source containerization of the NextGen framework to enable community-driven hydrology modeling - Arpita Patel; James Halgren; Zach Wills; Nels Frazier; Benjamin Lee; Joshua Cunningham; Jordan Laser; Mohammadsepehr Karimiziarani; Trupesh Patel; Giovanni Romero; Matthew Denno; Sam Lamont; et al. (Environmental Modelling & Software, 2025)

Parasite induced changes in contact behaviour is affected by parasitic status of group members - Alex M. M. Morris; Giles T. Innocent; Emma J. A. Cunningham; Darren P. Croft; Spiridoula Athanasiadou; Michael R. Hutchings; Lesley A. Smith (Behavioral Ecology and Sociobiology, 2025)
Understanding how parasitism may affect social behavior and social networks is key to understanding the impact of infection on a population. Infection can disrupt social networks by altering the behavior of both infected individuals (e.g. by reducing activity) and the behavior of uninfected individuals (e.g. avoiding sick individuals), both of which can have an impact on social group dynamics and parasite transmission. Here we test experimentally how parasitism affects social contact behavior and social network structure using a common parasite infection of sheep. Three treatment groups, each with 4 replicate social groups were established (i) Parasitised; all lambs were infected with a parasitic nematode, (ii) Non-parasitised; all lambs remained uninfected (iii) Mixed; part of each group were infected, and part of the group remained uninfected. Contact behaviours of each individual were recorded using proximity loggers during four phases of infection (pre-parasite, pre-patent, patent-parasite, post-parasite). We found infected individuals in the parasitised and mixed groups reduced contact frequency following infection. Despite the reduction in contacts between infected animals in the mixed group, non-infected individual’s maintained pre-parasite levels of social interactions with their infected conspecifics. These results demonstrate how infection can impact the social behavior of all animals within a group, and how the expression of behavioral change may depend on the parasitic status of all group members and the response of uninfected conspecifics. Significance statement Parasitism is known to influence animal behavior and social interactions; however groups of animals will often contain individuals of different parasitic status. Understanding the behavioral response of both infected and uninfected members of a group is important to predict the consequences of infection throughout a population. We show, under experimental conditions, that parasitism not only reduces the frequency of contacts between infected lambs at the earliest stages of infection in both mixed and single-parasitic state groups, but also the degree of behavior change exhibited by infected animals is influenced by the parasitic status of other individuals within the group. We also show that although infected animals in mixed-state groups had reduced contact frequency with their infected groupmates, non-infected animal’s maintained pre-infection levels of social interactions.

Brown Lemur (Eulemur spp.) Use of Olfaction, Memory, and Social Strategies to Obtain Cantaloupe - Elena P. Cunningham; Malvin N. Janal; Rachelle Wolk; Maria Gonzalez-Robles (International Journal of Primatology, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

The BirdLife Seabird Tracking Database: 20 years of collaboration for marine conservation - Ana P.B. Carneiro; Maria P. Dias; Bethany L. Clark; Elizabeth J. Pearmain; Jonathan Handley; Amy R. Hodgson; John P. Croxall; Richard A. Phillips; Steffen Oppel; Joanne M. Morten; Ben Lascelles; Cleo Cunningham; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Introducing the Ecosystem and Socioeconomic Profile, a Proving Ground for Next Generation Stock Assessments - S. K. Shotwell; K. Blackhart; C. Cunningham; E. Fedewa; D. Hanselman; K. Aydin; M. Doyle; B. Fissel; P. Lynch; O. Ormseth; P. Spencer; S. Zador (Coastal Management, 2023)

Occurrence and sources of microplastics on Arctic beaches: Svalbard - Tesni Lloyd-Jones; Jonathan J. Dick; Timothy P. Lane; Eoghan M. Cunningham; Konstadinos Kiriakoulakis (Marine Pollution Bulletin, 2023)

Can unique amino acid profiles guide adult salmon to natal streams? A comparison of streams sampled prior to and after the arrival of adult Pacific salmon - Andrew H. Dittman; Curry J. Cunningham; Thomas P. Quinn (Hydrobiologia, 2022)

Correction to: Childhood blood lead levels and environmental risk factors in Madagascar - Wyatt M. Champion; Adaline M. Buerck; Christopher Nenninger; Korede Yusuf; Luke J. P. Barrett; Lova Rakotoarisoa; Rinah Rakotondrazaka; Katherine Alfredo; Jeffrey Cunningham; Mahmooda Khaliq; James R. Mihelcic (Environmental Science and Pollution Research, 2022)

Childhood blood lead levels and environmental risk factors in Madagascar - Wyatt M. Champion; Adaline M. Buerck; Christopher Nenninger; Korede Yusuf; Luke J. P. Barrett; Lova Rakotoarisoa; Rinah Rakotondrazaka; Katherine Alfredo; Jeffrey Cunningham; Mahmooda Khaliq; James R. Mihelcic (Environmental Science and Pollution Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Drivers and physical processes of drought events over the State of São Paulo, Brazil - Abayomi A. Abatan; Simon F. B. Tett; Buwen Dong; Christopher Cunningham; Conrado M. Rudorff; Nicholas P. Klingaman; Rafael C. de Abreu (Climate Dynamics, 2022)
The State of São Paulo, Brazil (SSP) was impacted by severe water shortages during the intense austral summer drought of 2013/2014 and 2014/2015 (1415SD). This study seeks to understand the features and physical processes associated with these summer droughts in the context of other droughts over the region during 1961–2010. Thus, this study examines the spatio-temporal characteristics of anomalously low precipitation over SSP and the associated large-scale dynamics at seasonal timescales, using an observation-based dataset from the Climatic Research Unit (CRU) and model simulation outputs from the Met Office Hadley Centre Global Environment Model (HadGEM3-GA6 at N216 resolution). The study analyzes Historical and Natural simulations from the model to examine the role of human-induced climate forcing on droughts over SSP. Composites of large-scale fields associated with droughts are derived from ERA-20C and ERA-Interim reanalysis and the model simulations. HadGEM3-GA6 simulations capture the observed interannual variability of normalized precipitation anomalies over SSP, but with biases. Drought events over SSP are related to subsidence over the region. This is associated with reduced atmospheric moisture over the region as indicated by the analysis of the vertically integrated moisture flux convergence, which is dominated by reduced moisture flux convergence. The Historical simulations simulate the subsidence associated with droughts, but there are magnitude and location biases. The similarities between the circulation features of the severe 1415SD and other drought events over the region show that understanding of the dynamics of the past drought events over SSP could guide assessment of changes in risk of future droughts and improvements of model performance. The study highlights the merits and limitations of the HadGEM3-GA6 simulations. The model possesses the skills in simulating the large-scale atmospheric circulations modulating precipitation variability, leading to drought conditions over SSP.

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Multi-taxa spatial conservation planning reveals similar priorities between taxa and improved protected area representation with climate change - Rob Critchlow; Charles A. Cunningham; Humphrey Q. P. Crick; Nicholas A. Macgregor; Michael D. Morecroft; James W. Pearce-Higgins; Tom H. Oliver; Matthew J. Carroll; Colin M. Beale (Biodiversity and Conservation, 2022)
Protected area (PA) networks have in the past been constructed to include all major habitats, but have often been developed through consideration of only a few indicator taxa or across restricted areas, and rarely account for global climate change. Systematic conservation planning (SCP) aims to improve the efficiency of biodiversity conservation, particularly when addressing internationally agreed protection targets. We apply SCP in Great Britain (GB) using the widest taxonomic coverage to date (4,447 species), compare spatial prioritisation results across 18 taxa and use projected future (2080) distributions to assess the potential impact of climate change on PA network effectiveness. Priority conservation areas were similar among multiple taxa, despite considerable differences in spatial species richness patterns; thus systematic prioritisations based on indicator taxa for which data are widely available are still useful for conservation planning. We found that increasing the number of protected hectads by 2% (to reach the 2020 17% Aichi target) could have a disproportionate positive effect on species protected, with an increase of up to 17% for some taxa. The PA network in GB currently under-represents priority species but, if the potential future distributions under climate change are realised, the proportion of species distributions protected by the current PA network may increase, because many PAs are in northern and higher altitude areas. Optimal locations for new PAs are particularly concentrated in southern and upland areas of GB. This application of SCP shows how a small addition to an existing PA network could have disproportionate benefits for species conservation.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Ordovician volcanic rocks record rifting, Variscan metamorphism and gold mineralization processes (Truchas Syncline, NW Iberia, Spain) - L. González-Menéndez; F. Gómez-Fernández; J. K. Cunningham; S. Menéndez; P. Caldevilla; G. Gallastegui; A. Cuesta (Journal of Iberian Geology, 2021)

Cephalopods habitat and trophic ecology: historical data using snares penguin as biological sampler - H. R. Guímaro; D. R. Thompson; V. H. Paiva; F. R. Ceia; D. M. Cunningham; P. J. Moors; J. C. Xavier (Polar Biology, 2021)

Behavioral effects of benzylideneoxymorphone (BOM), a low efficacy µ opioid receptor agonist and a δ opioid receptor antagonist - Sanjana Mada; Lisa R. Gerak; Amélie Soyer; David R. Maguire; Zehua Hu; Vanessa Minervini; Christopher W. Cunningham; Charles P. France (Psychopharmacology, 2020)

Genetic assignment, diversity, and divergence of naturalised Acacia saligna (Fabaceae) in Tigray, Ethiopia - M. A. Millar; K. Mezgebe; N. Hagazi; P. Cunningham; M. Byrne (Tree Genetics & Genomes, 2020)

Physical activity and climate change attitudes - George Cunningham; Brian P. McCullough; Shelby Hohensee (Climatic Change, 2020)

Juggling a “junk-food” diet: responses of an urban bird to fluctuating anthropogenic-food availability - M. Stofberg; S.J. Cunningham; P. Sumasgutner; A. Amar (Urban Ecosystems, 2019)

Mutations in sorghum SBEIIb and SSIIa affect alkali spreading value, starch composition, thermal properties and flour viscosity - Stefanie Griebel; Richard P. Westerman; Adedayo Adeyanju; Charles Addo-Quaye; Bruce A. Craig; Clifford F. Weil; Suzanne M. Cunningham; Bhavesh Patel; Osvaldo H. Campanella; Mitchell R. Tuinstra (Theoretical and Applied Genetics, 2019)
Key message Seven novel alleles of SBEIIb and one allele of SSIIa co-segregated with the ASV phenotype and contributed to distinct starch quality traits important for food-processing applications. Abstract Sorghum is an important food crop for millions of people in Africa and Asia. Whole-genome re-sequencing of sorghum EMS mutants exhibiting an alkali spreading value (ASV) phenotype revealed candidate SNPs in Sobic.004G163700 and Sobic.010G093400 . Comparative genomics identified Sobic.010G093400 as a starch synthase IIa and Sobic.004G163700 as a starch branching enzyme IIb . Segregation analyses showed that mutations in Sobic.010G093400 or Sobic.004G163700 co-segregated with the ASV phenotype. Mutants in SSIIa exhibited no change in amylose content but expressed lower final viscosity and lower starch gelatinization temperature (GT) than starches from non-mutant plants. The sbeIIb mutants exhibited significantly higher amylose levels and starch GT and lower viscosity compared to non-mutant starches and ssIIa mutants. Mutations in SBEIIb had a dosage-dependent effect on amylose content. Double mutants of sbeIIb and ssIIa resembled their sbeIIb parent in amylose content, starch thermal properties and viscosity profiles. These variants will provide opportunities to produce sorghum varieties with modified starch end-use qualities important for the beer brewing and baking industries and specialty foods for humans with diabetes.

Correction to: Clinicians’ use of breast cancer risk assessment tools according to their perceived importance of breast cancer risk factors: an international survey - Anne Brédart; Jean-Luc Kop; Antonis C. Antoniou; Alex P. Cunningham; Antoine De Pauw; Marc Tischkowitz; Hans Ehrencrona; Marjanka K. Schmidt; Sylvie Dolbeault; Kerstin Rhiem; Douglas F. Easton; Peter Devilee; et al. (Journal of Community Genetics, 2019)

Independent lineages in a common environment: the roles of determinism and contingency in shaping the migration timing of even‐ versus odd‐year pink salmon over broad spatial and temporal scales - Krista B. Oke; Curry J. Cunningham; Thomas P. Quinn; Andrew P. Hendry (Ecology Letters, 2019)
Studies of parallel evolution are seldom able to disentangle the influence of cryptic environmental variation from that of evolutionary history; whereas the unique life history of pink salmon ( Oncorhynchus gorbuscha ) presents an opportunity to do so. All pink salmon mature at age two and die after breeding. Hence, pink salmon bred in even years are completely reproductively isolated from those bred in odd years, even if the two lineages bred in same location. We used time series (mean = 7 years, maximum = 74 years) of paired even‐ and odd‐year populations from 36 rivers spanning over 2000 km to explore parallelism in migration timing, a trait with a strong genetic basis. Migration timing was highly parallel, being determined almost entirely by local environmental differences among rivers. Interestingly, interannual changes in migration timing different somewhat between lineages. Overall, our findings indicate very strong determinism, with only a minor contribution of contingency.

Clinicians’ use of breast cancer risk assessment tools according to their perceived importance of breast cancer risk factors: an international survey - Anne Brédart; Jean-Luc Kop; Antonis C. Antoniou; Alex P. Cunningham; Antoine De Pauw; Marc Tischkowitz; Hans Ehrencrona; Marjanka K. Schmidt; Sylvie Dolbeault; Kerstin Rhiem; Douglas F. Easton; Peter Devilee; et al. (Journal of Community Genetics, 2019)

Response to Darting Primates: Steps toward Procedural and Reporting Standards - Elena P. Cunningham; Steve Unwin (International Journal of Primatology, 2018)

Eastern rockhopper penguins Eudyptes filholi as biological samplers of juvenile and sub-adult cephalopods around Campbell Island, New Zealand - J. C. Xavier; Y. Cherel; F. R. Ceia; J. P. Queirós; B. Guimarães; R. Rosa; D. M. Cunningham; P. J. Moors; D. R. Thompson (Polar Biology, 2018)

Corrections to: Use of the BOADICEA Web Application in clinical practice: appraisals by clinicians from various countries - Anne Brédart; Jean‑Luc Kop; Antonis C. Antoniou; Alex P. Cunningham; Antoine De Pauw; Marc Tischkowitz; Hans Ehrencrona; Sylvie Dolbeault; Léonore Robieux; Kerstin Rhiem; Douglas F. Easton; Peter Devilee; et al. (Familial Cancer, 2018)

Frequency, duration and severity of drought in the Semiarid Northeast Brazil region - S. S. B. Brito; A. P. M. A. Cunha; C. C. Cunningham; R. C. Alvalá; J. A. Marengo; M. A. Carvalho (International Journal of Climatology, 2018)
Drought is the natural disaster that impacts the greatest number of people and produces the most significant economic losses. This work presents a quantitative assessment of drought events occurred in the Semiarid region of Northeast Brazil during 1981–2016. The purpose of this study is to provide an overview of drought intensity for the last 36 years, analysing their severity, frequency and duration, considering hydro‐meteorological and agricultural aspects. To evaluate these two aspects, the 12‐month standardized precipitation index and the vegetation health index were considered to investigate drought characteristics. The definition of drought event for both these indices was performed regarding start and end month. In this context, drought duration is considered equal to the number of months of event, drought frequency is the number of events per time period and the drought severity is the absolute value of integral area below zero. Results show that the most severe and prolonged drought occurred in 2011–2016. In a clear contrast to previous droughts in past decades, during these last 5‐years period drought were more frequent, severe and affected a larger area with significant impacts for population, as well as economical activities.

Use of the BOADICEA Web Application in clinical practice: appraisals by clinicians from various countries - Anne Brédart; Jean-Luc Kop; Antonis C. Antoniou; Alex P. Cunningham; Antoine De Pauw; Marc Tischkowitz; Hans Ehrencrona; Sylvie Dolbeault; Léonore Robieux; Kerstin Rhiem; Douglas F. Easton; Peter Devilee; et al. (Familial Cancer, 2018)

Diverse foraging opportunities drive the functional response of local and landscape-scale bear predation on Pacific salmon - Thomas P. Quinn; Curry J. Cunningham; Aaron J. Wirsing (Oecologia, 2017)

Morphological, ecological and behavioural differentiation of sympatric profundal and pelagic Arctic charr (Salvelinus alpinus) in Loch Dughaill Scotland - O. E. Hooker; J. Barry; T. E. Van Leeuwen; A. Lyle; J. Newton; P. Cunningham; C. E. Adams (Hydrobiologia, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Warfare in stingless bees - C. Grüter; L. G. von Zuben; F. H. I. D. Segers; J. P. Cunningham (Insectes Sociaux, 2016)

Darting Primates in the Field: A Review of Reporting Trends and a Survey of Practices and Their Effect on the Primates Involved - Elena P. Cunningham; Steve Unwin; Joanna M. Setchell (International Journal of Primatology, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Can intense predation by bears exert a depensatory effect on recruitment in a Pacific salmon population? - Thomas P. Quinn; Curry J. Cunningham; Jessica Randall; Ray Hilborn (Oecologia, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Psittacine beak and feather disease in a free-living ring-necked parakeet (Psittacula krameri) in Great Britain - Ricardo C. C. Sa; Andrew A. Cunningham; Mark P. Dagleish; Nick Wheelhouse; Ann Pocknell; Nicole Borel; Hannah L. Peck; Becki Lawson (European Journal of Wildlife Research, 2014)

Effect of Fruit Scarcity on Use of Spatial Memory in a Seed Predator, White-faced Saki (Pithecia pithecia) - Elena P. Cunningham; Charles H. Janson (International Journal of Primatology, 2013)

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

Performance evaluation of a new fourth-generation HIV combination antigen–antibody assay - A. Mühlbacher; H. Schennach; J. van Helden; T. Hebell; G. Pantaleo; P. Bürgisser; C. Cellerai; P. Permpikul; M. I. Rodriguez; A. Eiras; F. Alborino; P. Cunningham; et al. (Medical Microbiology and Immunology, 2013)

Chemosensory responses of juvenile Coho salmon, Oncorhynchus kisutch, Dolly Varden, Salvelinus malma, and sculpins (Cottus spp.) to eggs and other tissues from adult Pacific salmon - Thomas P. Quinn; Andrew H. Dittman; Hannah Barrett; Curry Cunningham; Morgan H. Bond (Environmental Biology of Fishes, 2012)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

Atlantic transport variability at 25° N in six hydrographic sections - C. P. Atkinson; H. L. Bryden; S. A. Cunningham; B. A. King (Ocean Science, 2012)
In January and February 2010, a sixth transatlantic hydrographic section was completed across 25° N, extending the hydrographic record at this latitude to over half a century. In combination with continuous transport measurements made since 2004 at 26.5° N by the Rapid-WATCH project, we reassess transport variability in the 25° N hydrographic record. Past studies of transport variability at this latitude have assumed transport estimates from each hydrographic section to represent annual average conditions. In this study the uncertainty in this assumption is assessed through use of Rapid-WATCH observations to quantify sub-seasonal and seasonal transport variability. Whilst in the upper-ocean no significant interannual or decadal transport variability are identified in the hydrographic record, in the deep ocean transport variability in both depth and potential temperature classes suggests some interannual or decadal variability may have occurred. This is particularly striking in the lower North Atlantic Deep Water where southward transports prior to 1998 were greater than recent transports by several Sverdrups. Whilst a cooling and freshening of Denmark Straits Overflow Water has occurred which is coincident with these transport changes, these water mass changes appear to be density compensated. Transport changes are the result of changing velocity shear in the vicinity of the Deep Western Boundary Current.

An L 1-regularized logistic model for detecting short-term neuronal interactions - Mengyuan Zhao; Aaron Batista; John P. Cunningham; Cynthia Chestek; Zuley Rivera-Alvidrez; Rachel Kalmar; Stephen Ryu; Krishna Shenoy; Satish Iyengar (Journal of Computational Neuroscience, 2012)

The contribution of eastern-boundary density variations to the Atlantic meridional overturning circulation at 26.5° N - M. P. Chidichimo; T. Kanzow; S. A. Cunningham; W. E. Johns; J. Marotzke (Ocean Science, 2010)
We study the contribution of eastern-boundary density variations to sub-seasonal and seasonal anomalies of the strength and vertical structure of the Atlantic Meridional Overturning Circulation (AMOC) at 26.5° N, by means of the RAPID/MOCHA mooring array between April 2004 and October 2007. The major density anomalies are found in the upper 500 m, and they are often coherent down to 1400 m. The densities have 13-day fluctuations that are apparent down to 3500 m. The two strategies for measuring eastern-boundary density – a tall offshore mooring (EB1) and an array of moorings on the continental slope (EBH) – show little correspondence in terms of amplitude, vertical structure, and frequency distribution of the resulting basin-wide integrated transport fluctuations, implying that there are significant transport contributions between EB1 and EBH. Contrary to the original planning, measurements from EB1 cannot serve as backup or replacement for EBH: density needs to be measured directly at the continental slope to compute the full-basin density gradient. Fluctuations in density at EBH generate transport variability of 2 Sv rms in the AMOC, while the overall AMOC variability is 4.8 Sv rms. There is a pronounced deep-reaching seasonal cycle in density at the eastern boundary, which is apparent between 100 m and 1400 m, with maximum positive anomalies in spring and maximum negative anomalies in autumn. These changes drive anomalous southward upper mid-ocean flow in spring, implying maximum reduction of the AMOC, and vice-versa in autumn. The amplitude of the seasonal cycle of the AMOC arising from the eastern-boundary densities is 5.2 Sv peak-to-peak, dominating the 6.7 Sv peak-to-peak seasonal cycle of the total AMOC. Our analysis suggests that the seasonal cycle in density may be forced by the strong near-coastal seasonal cycle in wind stress curl.

Corrigendum to "Observed and simulated estimates of the meridional overturning circulation at 26.5° N in the Atlantic" published in Ocean Sci., 5, 575–589, 2009 - J. Baehr; S. Cunningham; H. Haak; P. Heimbach; T. Kanzow; J. Marotzke (Ocean Science, 2010)

A Robust Technique for Mapping Vegetation Condition Across a Major River System - S. C. Cunningham; R. Mac Nally; J. Read; P. J. Baker; M. White; J. R. Thomson; P. Griffioen (Ecosystems, 2009)

A six-year study of fire-related flowering cues and coexistence of two perennial grasses in a wet longleaf pine (Pinus palustris) savanna - J. Stephen Brewer; Amy L. Cunningham; Timothy P. Moore; Randell M. Brooks; Joanne L. Waldrup (Plant Ecology, 2009)

The differential diagnosis of vertical strabismus from prism cover test data using an artificially intelligent expert system - Anthony C. Fisher; Arvind Chandna; Ian P. Cunningham (Medical & Biological Engineering & Computing, 2007)

Levels of intra-host and temporal sequence variation in a large CO1 sub-units from Anisakis simplex sensu stricto (Rudolphi 1809) (Nematoda: Anisakisdae): implications for fisheries management - M. A. Cross; C. Collins; N. Campbell; P. C. Watts; J. C. Chubb; C. O. Cunningham; E. M. C. Hatfield; K. MacKenzie (Marine Biology, 2007)

New Resources for Marine Genomics: Bacterial Artificial Chromosome Libraries for the Eastern and Pacific Oysters (Crassostrea virginica and C. gigas) - Charles Cunningham; Jun-ichi Hikima; Matthew J. Jenny; Robert W. Chapman; Guang-Chen Fang; Chris Saski; Mats L. Lundqvist; Rod A. Wing; Pauline M. Cupit; Paul S. Gross; Greg W. Warr; Jeff P. Tomkins (Marine Biotechnology, 2006)

Characterisation of the European Marine Sites in South West England: The Fal and Helford Candidate Special Area of Conservation (cSAC) - W. J. Langston; B. S. Chesman; G. R. Burt; M. Taylor; R. Covey; N. Cunningham; P. Jonas; S. J. Hawkins (Hydrobiologia, 2006)

Anomalous gradient winds in the subtropical jet stream and interpretations of forecast failures - T. N. Krishnamurti; P. Cunningham; K. Rajendran (Meteorology and Atmospheric Physics, 2005)

The prevalence of escaped farmed salmon, Salmo salar L., in the River Ewe, western Scotland, with notes on their ages, weights and spawning distribution - J. R. A. BUTLER; P. D. CUNNINGHAM; K. STARR (Fisheries Management and Ecology, 2005)
The prevalence of escaped farmed Atlantic salmon, Salmo salar L., in the River Ewe, western Scotland, was assessed. After the establishment of smolt cages in the catchment and marine cages near the river mouth during 1986–1987, approximately 425 000 parr and smolts, and 122 000 growers have escaped. Between 1987 and 2001, farmed salmon occurred in the rod fishery in 13 of the 15 years, contributing at least 5.8% of the total catch, with a maximum annual frequency of 27.1%. It was estimated that P

Discrepancy Between Antennal and Behavioral Responses for Enantiomers of α-Pinene: Electrophysiology and Behavior of Helicoverpa armigera (Lepidoptera) - C. D. Hull; J. P. Cunningham; C. J. Moore; M. P. Zalucki; B. W. Cribb (Journal of Chemical Ecology, 2004)

Causes and Effects of Temporospatial Declines of Gyps Vultures in Asia - D. J. Pain; A. A. Cunningham; P. F. Donald; J. W. Duckworth; D. C. Houston; T. Katzner; J. Parry‐Jones; C. Poole; V. Prakash; P. Round; R. Timmins (Conservation Biology, 2003)

Compensation for herbivory by Cucumis sativus through increased photosynthetic capacity and efficiency - Vivien P. Thomson; Saul A. Cunningham; Marilyn C. Ball; Adrienne B. Nicotra (Oecologia, 2003)

Mechanisms of competition: thermal inhibition of tree seedling growth by grass - Marilyn C. Ball; J. Egerton; Jason L. Lutze; Vincent P. Gutschick; Ross B. Cunningham (Oecologia, 2002)

Refuting a controversial case of a human‐mediated marine species introduction - John P. Wares; Deena S. Goldwater; Bo Y. Kong; Clifford W. Cunningham (Ecology Letters, 2002)
Human activities have strongly impacted natural communities through the introduction of non‐native species in historical times. A frequently cited marine example is Littorina littorea , a common intertidal gastropod that was first reported in North America in 1840. The seemingly sudden appearance and rapid geographical spread of this species southward from Nova Scotia has led many researchers to consider L. littorea a human‐mediated species introduction. This is despite allozyme and subfossil evidence that the `European periwinkle' was in North America long before 1840. Our mitochondrial and nuclear DNA sequence data confirm that L. littorea has been in continuous residence in North America for at least 8000 years. It appears most likely that ecological interactions, rather than oceanographic or climatic forces, maintained the limited geographical distribution of L. littorea prior to the 19th century.

Reply to the comment by C.S. Spirakis - C. G. Cunningham; J. D. Rasmussen; T. A. Steven; R. O. Rye; P. D. Rowley; S. B. Romberger; J. Selverstone (Mineralium Deposita, 1999)

LONG DISTANCE OFFSHORE MOVEMENTS OF BOTTLENOSE DOLPHINS 1 - Randall S. Wells; Howard L. Rhinehart; Petra Cunningham; Joanne Whaley; Melody Baran; Chris Koberna; Daniel P. Costa (Marine Mammal Science, 1999)
A bstract Despite recent progress defining the morphological and genetic characteristics of forms of the bottlenose dolphin inhabiting offshore waters, little is known of their behavior or ranging patterns. Reports suggest that an “offshore form” exists between the 200‐ and 2,000‐m isobaths in distinct Gulf of Mexico and western North Atlantic stocks, while one or more coastal forms inhabit the waters inshore. Two opportunities to track rehabilitated adult male bottlenose dolphins with satellite‐linked transmitters occurred in 1997. “Rudy” stranded in NW Florida and was released in the Gulf of Mexico off central west Florida. He moved around Florida and northward to off Cape Hatteras, NC, covering 2,050 km in 43 d. “Gulliver” stranded near St. Augustine and was released off Cape Canaveral, FL. He moved 4,200 km in 47 d to a location northeast of the Virgin Islands. Gulliver swam through 5,000‐m‐deep waters 300 km offshore of the northern Caribbean islands, against the North Equatorial Current. These records expand the range and habitat previously reported for the offshore stock of bottlenose dolphins inhabiting the waters off the southeastern United States, underscore the difficulties of defining pelagic stocks, illustrate the success of rehabilitation efforts, indicate the value of follow‐up monitoring of rehabilitated and released cetaceans, and expand our understanding of the long‐range movement capabilities of a dolphin species more commonly thought of as a resident in coastal waters.

Dissipation of Phloxine B and Uranine in Protein Bait Sprayed in a Coffee Field for the Suppression of Mediterranean Fruit Fly - J. P. Alcantara-Licudine; R. T. Cunningham; N. J. Liquido; G. T. McQuate; Q. X. Li (Bulletin of Environmental Contamination and Toxicology, 1999)

Insulitis and mechanisms of disease resistance: studies in an animal model of insulin dependent diabetes mellitus - A. J. Bone; P. R. Hitchcock; D. J. Gwilliam; J. M. Cunningham; J. Barley (Journal of Molecular Medicine, 1999)

Sheep CD4 + αβ T cells express novel members of the T19 multigene family - Meredith A. O'Keeffe; S. A. Metcalfe; Craig P. Cunningham; I. D. Walker (Immunogenetics, 1999)

The captive rearing of threatened Orthoptera: a comparison of the conservation potential and practical considerations of two species' breeding programmes at the Zoological Society of London - P. Pearce-Kelly; R. Jones; D. Clarke; C. Walker; P. Atkin; A.A. Cunningham (Journal of Insect Conservation, 1998)

Hydrothermal uranium deposits containing molybdenum and fluorite in the Marysvale volcanic field, west-central Utah - C. G. Cunningham; J. D. Rasmussen; T. A. Steven; R. O. Rye; P. D. Rowley; S. B. Romberger; J. Selverstone (Mineralium Deposita, 1998)

Anatomical evidence for androdioecy in the clam shrimp Eulimnadia texana - Naida Zucker; Mark Cunningham; Henry P. Adams (Hydrobiologia, 1997)

Hydrolysis of oleylanilide in the rat - V. J. Cunningham; S. P. Tucker; E. Bailey (Archives of Toxicology, 1983)

Variation in the hepatotoxic effects of carbon disulphide between different strains of rat - S. P. Tucker; D. P. Lovell; A. A. Seawright; V. J. Cunningham (Archives of Toxicology, 1980)

Erratum - I. L. Nonnecke; W. E. Torfason; L. C. Young; P. Nandi; S. P. Raychaudhuri; Helen H. Cunningham; Mary V. Zaehringer; Walter C. Sparks; Clarence J. Miller; Richard L Sawyer (American Journal of Potato Research, 1966)

Report of the potato utilization committee - C. E. Cunningham; O. C. Turnquist; D. R. Isleib; E. J. Wheeler; R. L. Sawyer; P. A. Xander; W. C. Sparks; R. H. Treadway (American Journal of Potato Research, 1959)

Potato vine killing methods as related to rate of kill, vascular discoloration, and virus disease spread - C. E. Cunningham; P. J. Eastman; Michael Goven (American Journal of Potato Research, 1952)